Programma: 28 mei Salad; 30 mei Defunkt Music Inc; 31 mei H-Blockx; 1 juni Peranha Party; 2 juni The Mystic Revealers; 3 juni Sjako!, Moondogs, The Blue Man Can
Programma: 28 mei Salad; 30 mei Defunkt Music Inc; 31 mei H-Blockx; 1 juni Peranha Party; 2 juni The Mystic Revealers; 3 juni Sjako!, Moondogs, The Blue Man Can.